Future of Colorectal Cancer Screening: From One-Size-FITs-All to Tailor-Made - Kortlever, Tim; van der Vlugt, Manon; Dekker, Evelien (Frontiers in Gastroenterology, 2022)
Screening for colorectal cancer (CRC) and its precursor lesions, advanced adenomas (AA), has been shown to effectively reduce CRC-related mortality. However, the method of CRC screening varies among countries. Primary colonoscopy screening is the most effective screening option from an individual point of view, but it is costly and at a population level the participation rates are relatively low. Repeated screening with a fecal immunochemical test (FIT) is a non-invasive and inexpensive way to select individuals at high risk for CRC for colonoscopy. Despite its widespread use and mostly high participation rates, FIT is not perfect. Due to the low sensitivity for detecting CRC and its precursor lesions, its effectiveness is limited. Besides, the false positivity rate of FIT is relatively high resulting in unnecessary colonoscopies and anxiety and risks among FIT-positives. To improve the effectiveness of CRC screening, new strategies need to be developed. In the past years much research has been undertaken on risk-based screening or risk models. These include tests consisting of multiple risk factors and/or biomarkers (cross-sectional risk models) or tools that predict the risk of future CRC and may be used to offer personalized screening strategies (longitudinal risk models). We will provide an overview of the developments on risk models for CRC screening and discuss some of the obstacles that they need to overcome to enable widespread implementation in existing CRC screening programs.